Costly, but (relatively) ineffective? An assessment of Germany's temporary VAT rate reduction during the Covid-19 pandemic - Victoria Baudisch; Matthias Neuenkirch (Universität Trier, Fachbereich IV - Volkswirtschaftslehre, 2023)
We evaluate Germany's temporary value-added tax (VAT) rate reduction as a tool to stimulate consumer spending during the Covid-19 pandemic using a comparative case study approach. We construct a credible counterfactual for Germany in a two-step procedure. First, we carry out a careful pre-selection of the donor pool countries to obtain a control group that is highly similar to Germany regarding important post-treatment characteristics. Second, we apply a reweighting scheme on the pre-selected donor countries. The synthetic control group only differs from Germany in the way that it did not implement the temporary VAT rate reduction. Our results indicate that the German VAT cut policy and partial VAT reductions in other countries were relatively ineffective in stimulating consumption with regards to their costs when compared to other measures such as (targeted) direct cash transfers. We attribute this to the fact that direct cash transfers are more comprehensible, salient, and actionable, in particular, in a dynamic environment with high uncertainty induced by unclear future economic prospects.
Keywords: E21; E62; E65; H31; 330; Consumption; Covid-19; Synthetic Control; Temporary VAT Cut; Unconventional Fiscal Policy